Gerador LARL com suporte a resolução de conflitos - Leonardo Teixeira Passos (2007)
Despite all the advance brought by LALR parsing method by DeRemer in the late 60's, conflicts continue to be removed in a non-productive way, by means of analysis of a huge amount of textual and low level data dumped by the parser generator tool. For the purpose of changing this scenario, we present a parser generator capable of automatically removing some types of conflicts, along with a supported methodology that guides the process of manual removal. We also discuss the internal algorithms and how the created parsers are compact in terms of memory usage.